Using social media in the news reportage of War & Conflict: Opportunities and Challenges - Sacco, Vittoria; Bossio, Diana (My University, 2015)
Based on interviews with Swiss journalists who specialise in war and international reportage, this article investigates the extent to which social media impacts on reportage of war and conflict. The interviews examine journalists’ perceptions of the threats and opportunities posed by use of social media in reporting conflict, by investigating how journalists position themselves and their practices within this new media ecosystem. In particular, the interviews explore whether challenges to professional journalism encountered in previous studies of reportage of war and conflict are overcome by the use of social media. It explores if social media can mitigate the effects of military and government restriction of information, changing newsroom dynamics and issues of audience engagement in reportage of conflict. The findings highlight that in the context of war and conflict the dynamism creates opportunities for fast, news dissemination, pluralised voices in reportage and extended audience reach. However, reporters must also negotiate the complexities that fast, multi-medium and multi-sourced information create for reporting practices, especially in terms of verification of information and contextualisation. Thus this article argues that although social media adds dynamism to journalistic environments, this dynamism also brings new levels of complexity to journalistic practice that professional media workers must negotiate.
Keywords: social media; war & conflict; journalistic practice